2011
DOI: 10.1123/jpah.8.s1.s26
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Community Providers to Create More Active After-School Environments: Results From the Ontario CATCH Kids Club Implementation Project

Abstract: This paper offers support for PA programs that focus on inclusivity and enjoyment and emphasize the important role of staff competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 15 publications
4
61
0
Order By: Relevance
“…Similar findings resulted from a study conducted in Canada were it was found that by involving adult leaders in the promotion of PA the amount of time children spend performing these activities increased, as long as the leaders had the necessary competencies for instructing the children 34 .…”
Section: Discussionsupporting
confidence: 76%
“…Similar findings resulted from a study conducted in Canada were it was found that by involving adult leaders in the promotion of PA the amount of time children spend performing these activities increased, as long as the leaders had the necessary competencies for instructing the children 34 .…”
Section: Discussionsupporting
confidence: 76%
“…10 These studies have used a variety of approaches including delivering physical activity curriculum, environmental changes driven by policy adoption and programs tailored to the cultural needs of afterschool programs but have resulted in limited success. Some studies have reported minimal increases in child activity 11-13 while other studies have reported no increase in child activity. 14,15 We hypothesize that, one reason for the limited success of these studies may be that staff are not displaying behaviors linked to child physical activity, and outlined in HEPA Standards, at a sufficient level to affect child physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…8 This study was a natural experiment with the ASPs initiating the purchase and subsequent implementation of the CKC. Within a subsample of 34 YMCAs and 6 Boys and Girls Clubs research staff collected systematic observation data of children's physical activity using SOFIT.…”
Section: Efficacy/effectiveness Of Existing Effortsmentioning
confidence: 99%